Determination of effective growth time for zinc oxide nanorods using chemical solution deposition. (December 2015) - Kim, Kyung Ho; Umakoshi, Tomoyuki; Abe, Yoshio; Kawamura, Midori; Kiba, Takayuki
Abstract: Zinc oxide (ZnO) nanorods were grown on a ZnO seed layer using chemical solution deposition, and their growth behavior over various timescales was investigated. The structural properties of the nanorods were investigated using x-ray diffraction (XRD) and field emission scanning electron microscopy (FESEM), and the pH of the solution was measured both before and after the reaction process. It was observed that the nanorods grew in two stages, with the first stage from 0 to 6 h time and the second stage at 12–24 h of time. When they were given 24 h of reaction time, the length and aspect ratio of the nanorods reached ∼2.6 μm and ∼54, respectively. The pH value of the solution changed during the whole process, and on reaching a pH value ∼8.1 after 36 h, the nanorods exhibited very stable size dimensions. The most effective growth time to yield nanorods with high aspect ratios was determined to be 24 h. Highlights: ZnO nanorods were fabricated using CSD with various reaction times up to 36 h. The growth of the nanorods was two-stage process. During the whole process, the pH value of the solution changed and reached at ∼8.1. The effective time was 24 h for the growth of the nanorods with high aspect ratio.